Factores estresantes en adultos mayores con diabetes e hipertensión que acuden al Puesto de Salud de Timbara - Ordoñez Montaño, Gabriela Alejandra (2022)
Stress is a feeling that is part of our daily life, when there are situations that surpass our demands, overloading our normal state and affecting both our physical and mental health. The present work of curricular integration aimed to determine the stressors in older adults with diabetes and hypertension who come to the Timbara Health Post, and implement resilience strategies to control stressors. The present research was quantitative, applied and cross-sectional. The sample consisted of 44 older adults diagnosed with diabetes and hypertension, who were surveyed to determine sociodemographic characteristics and determine which stressors affect the health of the population. Socio-demographic results showed that 50% were male and 50% female, with an age range of 65-74 years. 70,45% are married, 34.09% of the respondents live in the Tunanza neighborhood and the rest are distributed around the parish, with 100% of the respondents attended primary school only. In terms of economic activity, 40.91% of women are housewives and 31.81% of men are engaged in agriculture. Based on the research conducted, it was possible to show that the factors that most cause stress in older adults are: social, psychological and physiological. Therefore, 72.72% of the population feels stressed when leading a routine lifestyle, 90.91% feel that their mental health status is affected by fear of being infected with the virus SARS-COVID-2 and 84.09% of older adults feel that stress affects their physical health more. In conclusion, older adults who come to the Timbara health post are stressed by different situations that they have to endure day after day when dealing with these factors. Consequently, resilience strategies are implemented such as breathing exercises, muscle relaxation, physical exercises and education activities that allow controlling stress in order to improve their lifestyle. Keywords: stress, resilience, stressors, health, strategies.